If y varies directly with x, it can be written as y = kx, where k is the constant of variation.
Given that y equals 14 when x equals -4, we can substitute these values into the equation to find k.
14 = k(-4)
Dividing both sides by -4, we get:
k = -3.5
Now we can use this value of k to find the value of y when x equals -6.
y = (-3.5)(-6)
y = 21
Therefore, when x equals -6, y equals 21.
suppose why varies directly with X and why equals 14 when X equals -4 what is the value of Y when X equals -6
1 answer